Subcutaneous injection of genetically engineered exosomes for androgenic alopecia treatment - Yukun Liu; Yukun Liu; Yukun Liu; Yonghong Liu; Jing Zhao; Tianyi Deng; Yinyin Ben; Ruitao Lu; Xusha Zhou; Runbin Yan; Xiaoqing Chen; Jian V. Zhang; et al. (Frontiers in Bioengineering and Biotechnology)
Androgenetic alopecia (AGA) is a common disorder that negatively impacts quality of life but remains challenging to treat effectively. The hair loss observed in AGA is the consequence of a gradual reduction in the duration of the anagen phase concomitant of the miniaturization of the hair follicles and subsequent atrophy. This process of miniaturization is associated with abnormalities in the Dihydrotestosterone (DHT) induced dermal papilla cells (DPCs). DHT induces DPCs senescence and promotes apoptosis of vascular endothelial cells and keratinocytes via the DPCs paracrine pathway, which ultimately leads to follicular miniaturization. In this study, we developed a multifunctional exosome-based targeted delivery platform, designated as EX104, through the engineering of HEK-293 cells to express a combination of therapeutical molecules, including WNT10B, VEGFA, and FGF7. EX104 reversed the hair follicle miniaturization phenotype in DHT-induced DPCs. Furthermore, it demonstrated significant hair growth-promoting effects in the murine model of androgenetic alopecia by remodeling the follicular microenvironment and restoring miniaturized hair follicles. Topical EX104 application demonstrated comparable hair growth promotion to first-line minoxidil, while significantly outperforming it in stimulating capillary growth and follicular proliferation. EX104 represents a promising and innovative strategy for AGA management and follicular regenerative therapy.